The effect of a formulation containing honey, black cumin, propolis and royal jelly on blood glucose level and pancreatic ï¢-cells of streptozotocin-induced diabetic rats - Setyo Purwono,Sitarina Widyarini,Mustofa, Sunyoto, Umi Mahmudah, Sindu Oktivasari,Eti Nurwening Shol (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
A formulation containing 40% of honey, 30% of black cumin, 20% of propolis and 10% of royaljelly has been available in the market for the treatment of diabetes. Although each content ofthe formulation is proven to possess antioxidant and antihyperglycemic activities, its combinationeffect has not been evaluated yet. The aim of this study was to evaluate the effect of thisformulation on blood glucose level and pancreatic ï¢-cells of streptozotocin (STZ)-induced diabeticrats. Thirty six male Wistar rats (Rattus novergicus) aged 11 weeks with body weight 100-150 gwere used in this study. The rats were divided into 6 groups with 6 rats in each group. Group 1was non diabetic rats that were given aquadest. Group 2 was diabetic rats that were givenaquadest. Group 3 was diabetic rats that were given metformin at dose of 45 mg/kg BW. Group4-6 were diabetic rats that were given formulation tested at dose of 3, 6 and 12 mL/kg BW,respectively. All rats were induced by intraperitoneal injection of STZ at 60 mg/kg BW anddiabetic rats were then orally administered the formulation tested or metformin twice daily for14 days. Blood glucose level was monitored on day 10 and 17 after STZ induction. Rats weresacrificed and pancreas samples were taken for histopathological examination. The results showedthat the blood glucose level decreased significantly after seven days of treatment with metforminor fomulation tested and continued after 14 days of treatment. The blood glucose level ofdiabetic rats after 14 days of treatment returned to the normal level. The vacuolization of thepancreatic ï¢-cells of diabetic rats treated with metformin or with formulation tested were lowerthan untreated diabetic rats but still higher than non diabetic rats. In conclusion, the formulationtested has antihyperglicemic and protective effect on ï¢-cells damage in diabetic rats.Keywords: diabetic rats - honey - black cumin - propolis - royal jelly - antihyperglicemic